Pengembangan,Media Pembelajaran.Menggunakan Adobe Flash CS6 Mata Pelajaran Geografi Materi Flora dan Fauna Diindonesia dan Dunia Kelas XI SMA,Negeri 1 Lemito - Latif, Ramli; Nurfaika, Nurfaika; Liayong Pratama, M. Iqbal (-, 2025)
Adobe Flash is a graphic software that was originally developed by Macromedia Corporation, a company that focuses on developing web-based animation applications. This application has great potential in the world of education because of the ease of design, content management, and wide access for various user groups. This study aims to design and develop interactive learning media using Adobe Flash CS6. The method used is research and development (Research and Development) with the ADDIE model approach, which consists of five main stages: analysis, design, development, implementation, and evaluation. With an assessment of material experts of 80%, product experts of 97.89%, and learning experts of 88.57%, the results of the study indicate that the media created has gone through a validation process. With a response rate of 94.93% to the use of interactive media based on Adobe Flash CS6 to present Indonesian and world flora and fauna material, grade XI students of SMA Negeri 1 Lemito who participated in the media trial also showed very positive results. Thus, it can be said that the teaching materials created are considered practical and efficient to use, especially in teaching Basic Geography Knowledge content.